2001
DOI: 10.1007/3-540-45468-3_8
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method for Constructing Optimal Statistical Shape Models

Abstract: Statistical shape models show considerable promise as a basis for segmenting and interpreting images. A major drawback of the approach is the need to establish a dense correspondence across a training set of segmented shapes. By posing the problem as one of minimising the description length of the model, we develop an efficient method that automatically defines a correspondence across a set of shapes. As the correspondence does not use an explicit ordering constraint, it generalises to 3D shapes. Results are g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A number of automated shape registration and model building methods have been proposed [7], [4], [5], [6]. These approaches either establish correspondences between geometric features, such as critical points of high curvature [5]; or find the "best" corresponding parametrization model by optimizing some criterion, such as minimizing accumulated Euclidean Distance [4], [6], Minimum Description Length [7], or Spline Bending Energy [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of automated shape registration and model building methods have been proposed [7], [4], [5], [6]. These approaches either establish correspondences between geometric features, such as critical points of high curvature [5]; or find the "best" corresponding parametrization model by optimizing some criterion, such as minimizing accumulated Euclidean Distance [4], [6], Minimum Description Length [7], or Spline Bending Energy [6].…”
Section: Introductionmentioning
confidence: 99%
“…These approaches either establish correspondences between geometric features, such as critical points of high curvature [5]; or find the "best" corresponding parametrization model by optimizing some criterion, such as minimizing accumulated Euclidean Distance [4], [6], Minimum Description Length [7], or Spline Bending Energy [6]. Both geometric feature based and explicit parameterization based registration methods are not suitable for incorporating region intensity information.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility to automate this is to use the parameterization of shapes, like spherical harmonics [3]. Davies et al found the point correspondence via an optimization problem [5]. Rueckert et al applied PCA to the deformation fields that were got by registering the volumes in a training set to a reference volume [6].…”
Section: Introductionmentioning
confidence: 99%